Ocean turbulent boundary-layer influence on ice crystal behaviour beneath fast ice in an Antarctic ice shelf water plume: The “dirty ice” - Stevens, Craig; Robinson, Natalie; O’Connor, Gabby; Grant, Brett (Frontiers in Marine Science, 2023)
The oceanic connection between ice shelf cavities and sea ice influences sea ice development and persistence. One unique feature in regions near ice shelves is the potential for sea ice growth due to crystal accretion on its underside. Here we present observations of ocean boundary-layer processes and ice crystal behaviour in an Ice Shelf Water outflow region from the Ross/McMurdo Ice Shelves. From a fast ice field camp during the Spring of 2015, we captured the kinematics of free-floating relatively large (in some cases 10s of mm in scale) ice crystals that were advecting and then settling upwards in a depositional layer on the sea ice underside (SIPL, sub-ice platelet layer). Simultaneously, we measured the background oceanic temperature, salinity, currents and turbulence structure. At the camp location the total water depth was 536 m, with the uppermost 50 m of the water column being in-situ super-cooled. Tidal flow speeds had an amplitude of around 0.1 m s-1 with dissipation rates in the under-ice boundary layer measured to be up to ε=10-6 W kg-1. Acoustic sampling (200 kHz) identified backscatter from large, individually identifiable suspended crystals associated with crystal sizes larger than normally described as frazil. Measurement of crystals in the SIPL found dimensions of the range 5-200 mm with an average of 93-101 mm depending on the year. The existence and settlement of crystals has implications for understanding SIPL evolution, the structure of sea ice, as well as the fate of Ice Shelf Water.